Marketing strategy in "Bakpiapia Djogja" food product packaging design - Prathisara, Gibbran Prathisara; Masduki, Anang Masduki (COMMICAST, 2023)
Reviewing the role of packaging in today's snack products, the packaging function is not only to protect the existing products in it but to grow more broadly with the addition of functional values, among others is as a means of communication between producers and consumers, namely as communications media that describe or reflect the product, brand image, and also as part of the promotion with the consideration that the packaging is easy to see, understand, and remember. Bakpiapia Djogja, a bakpia product in Yogyakarta, has innovated different packaging designs from competitors to increase consumer awareness towards bakpia products from Bakpiapia Djogja. This makes Bakpiapia Djogja have creative and different image compared with other competitors. From the marketing aspect of Bakpiapia Djogja packaging design, try to be an integral part and place it precisely at the beginning of the marketing concept. Packaging Bakpiapia Djogja has been aimed at specific markets, namely young people and tourists. Bakpiapia Djogja emphasizes the visual aspect of packaging to give more value to consumer consideration.